2023
DOI: 10.2196/47305
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Large Language Model ChatGPT on the National Nurse Examinations in Japan: Evaluation Study

Abstract: Background ChatGPT, a large language model, has shown good performance on physician certification examinations and medical consultations. However, its performance has not been examined in languages other than English or on nursing examinations. Objective We aimed to evaluate the performance of ChatGPT on the Japanese National Nurse Examinations. Methods We evaluated the percentages of correct answers provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Several studies assessed AI model performance in non-English languages with variable results despite the overall trend of below bar performance in non-English languages. For example, Taira et al tested ChatGPT performance in the Japanese National Nursing Examination in Japanese language in ve consecutive years [43]. Despite approaching the passing threshold in four years and passing the 2019 exam, the results indicated the relative weakness of ChatGPT in Japanese [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies assessed AI model performance in non-English languages with variable results despite the overall trend of below bar performance in non-English languages. For example, Taira et al tested ChatGPT performance in the Japanese National Nursing Examination in Japanese language in ve consecutive years [43]. Despite approaching the passing threshold in four years and passing the 2019 exam, the results indicated the relative weakness of ChatGPT in Japanese [43].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Taira et al tested ChatGPT performance in the Japanese National Nursing Examination in Japanese language in ve consecutive years [43]. Despite approaching the passing threshold in four years and passing the 2019 exam, the results indicated the relative weakness of ChatGPT in Japanese [43]. Nevertheless, attributing this result to language limitations alone is challenging, given the superior performance of ChatGPT-4 in Japanese language compared to medical residents in the Japanese General Medicine In-Training Examination, as reported by Watari et al [44].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, prior research on the Japanese national medical examinations found that the performance gap between AI and humans widened with increasing question difficulty [ 12 ]. Indeed, AI models such as GPT-4 have achieved the proficiency level required to pass even highly challenging certification examinations that often pose challenges for many humans [ 2 - 5 , 11 , 12 ]. Because common clinical scenarios often follow a distinct framework or pattern, AI’s rule-based responses have the potential to surpass human performance [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This assessment is especially relevant because Japanese is considered among English natives as one of the most challenging languages to master [ 10 ]. Interestingly, it has been suggested that GPT-3.5, the precursor to GPT-4, has achieved passing grades on the Japanese Nursing Licensing examination [ 11 ]. In the latest Japanese national medical licensing examination in February 2023, GPT-4 attained passing levels while GPT-3.5 showed that it is not far behind the passing criteria [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that ChatGPT can assist nurses in medical record documentation [ 37 ], enhance patient education resources [ 38 ], and successfully boost patient communication efficiency [ 37 ]. One study discovered that ChatGPT successfully passed the Japanese registered nursing licensure test [ 39 ]. While experienced nursing educators produce National Council Licensure Examination for Registered Nurses (NCLEX-RN) questions for daily test practice, the actual NCLEX-RN exam uses computer-generated questions based on the college’s current response scenario.…”
Section: The Impact Of Chatgpt On Nursing Educationmentioning
confidence: 99%